Encoding Newton’s Alchemical Library: Integrating Traditional Bibliographic and Modern Computational Methods - Meridith Beck Mink (OpenEdition, 2020)
The Chymistry of Isaac Newton (http://chymistry.org) project team has digitized and encoded, following the TEI Guidelines, the complete corpus of Newton’s alchemical manuscripts, which total more than two thousand pages and over one million words. Newton cited more than five thousand published and unpublished works in these manuscripts; many of his annotations reference items in his own library, as he was an exceptionally dedicated reader of alchemical texts. Newton’s extensive citations and annotations provide a window into his alchemical research and practices, and serve as the basis for our authoritative bibliography of his alchemical sources. The bibliography is being developed as both a stand-alone reference work and an integrated resource with the alchemical manuscripts, providing additional context for Newton’s citations and florilegia. Once finished, the bibliography will provide complete, structured citations—which often would appear very abbreviated or incomplete in the manuscripts—that can be formatted to comply with modern bibliographic conventions and bibliographic management systems. Our bibliography will also link to digitized online versions of the source texts available through Early English Books Online, HathiTrust Digital Library, and other digital repositories. The citations include quasi-facsimile title page transcription, a technique used for bibliographic description of rare books, to enable richer forms of citation analysis. By analyzing the citations, we will be able to date Newton’s manuscripts, cluster manuscripts that cite the same or related sources, and, ultimately, generate network graphs that will reveal connections between the cited authors and texts and how they influence Newton’s own ideas and work.